Pengaruh Pelatihan Kerja dan Disiplin Kerja Terhadap Produktivitas Kerja Karyawan di PT Maan Ghodaqo Shiddiq Lestari (MAAQO) Jombang - Nur Fadilah (BIMA : Journal of Business and Innovation Management, 2020)
This study aims to determine wheater or not the influence of job training and work discipline on the work productivity of employees at PT MAAQO. The type of research used in this study is quantitative research with an associative approach. The sampling technique used was saturated samples with a sample of 76 employees at PT MAAQO. This sudy uses the technique of collecting data on obsevations, interviews, questionnaires and documentation. Data analysis techniques used are multiple linear regression analysis, t test and f test with results that show that: (1) Job training and work discipline simultaneously affect work productivity at PT MAAQO. (2) Work discipline partially has a positive and significant effect on work productivity at PT MAAQO. (3) Job training and work discipline simultaneously affect work productivity at PT MAAQO.